A narrative review on cervical artery dissection-related cranial nerve palsies - Dejakum, Benjamin; Kiechl, Stefan; Knoflach, Michael; Mayer-Suess, Lukas (Frontiers in Neurology, 2024)
Objective: To emphasize on the importance of cranial nerve (CN) palsies in spontaneous cervical artery dissection. Methods: Search-term based literature review (“cervical artery dissection”, “cranial nerve palsy”). English and German articles until October 2023 were considered. Results: Cranial nerve (CN) palsy in spontaneous cervical artery dissection is evident in about 10% of cases. In literature, isolated palsies of CN II, III, VII, IX, X, and XII have been reported, while CN XI palsy only occurs in combination with other lower cranial nerve palsies. Dissection type and mural hematoma localisation are specific to affected CN as CN palsies of II or III are solely evident in those with steno-occlusive vessel pathologies located at more proximal segments of ICA, while those with CN palsies of IX, X, XI and XII occur in expansive sCeAD at more distal segments. This dichotomization emphasizes the hypothesis of a different pathomechanism in CN palsy in sCeAD, one being hypoperfusion or microembolism (CN II, III, VII) and the other being a local mass effect on surrounding tissue (CN IX-, X-, XI, XII). Clinically, the distinction between peripheral palsies and those caused by brainstem infarction is difficult. This differentiation is key, as, according to the reviewed cases, peripheral cranial nerve palsies in spontaneous cervical artery dissection patients mostly resolve completely over time, while those due to brainstem stroke do not, making cerebrovascular imaging appraisal essential. Conclusion: It is important to keep dissections as cause of peripheral CN palsies as well as the proper diagnostic pathways in mind as they can guide clinicians to an early diagnosis harbouring the chance of primary stroke prevention.